Investigations into the Nature of Halogen Bonding Including Symmetry Adapted Perturbation Theory Analyses - Riley, Kevin E; Hobza, Pavel (Journal of chemical theory and computation, 2008)
In recent years it has been recognized that, because of their unique properties, halogen bonds have tremendous potential in the development of new pharmaceutical compounds and materials. In this study we investigate the phenomenon of halogen bonding by carrying out ab initio calculations on the halomethane-formaldehyde complexes as well as the fluorine substituted FnH3-nCX···OCH2 dimers, where the halogen bonding halogens (X) are chlorine, bromine, and iodine. Coupled cluster (CCSD(T)/aug-cc-pVTZ) calculations indicate that the binding energies for these type of interactions lie in the range between -1.05 kcal/mol (H3CCl···OCH2) and -3.72 kcal/mol (F3CI···OCH2). One of the most important findings in this study is that, according to symmetry adapted perturbation theory (SAPT) analyses, halogen bonds are largely dependent on both electrostatic and dispersion type interactions. As the halogen atom involved in halogen bonding becomes larger the interaction strength for this type of interaction also gets larger and, interestingly, more electrostatic (and less dispersive) in character. Halogen bonding interactions also become stronger and more electrostatic upon substitution of (the very electronegative) fluorines onto the halomethane molecule.